Assessment of the Microbiota in Microdissected Tissues of Crohn's Disease Patients. (7th December 2011) - De Hertogh, Gert; Lemmens, Bart; Verhasselt, Peter; de Hoogt, Ronald; Sagaert, Xavier; Joossens, Marie; Van Assche, Gert; Rutgeerts, Paul; Vermeire, Severine; Aerssens, Jeroen
Abstract : The microbiota of the gastrointestinal tract is frequently mentioned as one of the key players in the etiopathogenesis of Crohn's disease (CD). Four hypotheses have been suggested: the single, still unknown bacterial pathogen, an abnormal overall composition of the bowel microbiota ("dysbiosis"), an abnormal immunological reaction to an essentially normally composed microbiota, and increased bacterial translocation. We propose that laser capture microdissection of selected microscopic structures, followed by broad-range 16S rRNA gene sequencing, is an excellent method to assess spatiotemporal alterations in the composition of the bowel microbiota in CD. Using this approach, we demonstrated significant changes of the composition, abundance, and location of the gut microbiome in this disease. Some of these abnormal findings persisted even after macroscopic mucosal healing. Further investigations along these lines may lead to a better understanding of the possible involvement of the bowel bacteria in the development of clinical Crohn's disease.